2013
DOI: 10.1063/1.4817498
|View full text |Cite
|
Sign up to set email alerts
|

Theory and synthesis of bilayer graphene intercalated with ICl and IBr for low power device applications

Abstract: Graphene intercalation materials are potentially promising for the implementation of the ultra-low power, excitonic-condensate-based Bilayer pseudoSpin Field-Effect Transistor (BiS-FETs) concept, as well as other novel device concepts requiring a graphene interlayer dielectric. Using density functional theory (DFT) we study the structural and electronic properties of bilayer graphene intercalated with iodine monochloride (ICl) and iodine monobromide (IBr).We determine the structural configuration of ICl and IB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The experimental realization of intercalation of molecular and atomic species into quasi-free FLG was recently reported for K, Rb [195], ICl and IBr [196] using the vapour-phase method. In particular, partial intercalation of K and Rb was performed by means of a two-zone vapour-phase method at 210 and 160 • C, whereas the intercalation of ICl and IBr requires relatively low temperatures (just 35 • C).…”
Section: Intercalated Quasi-free Few-layer Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…The experimental realization of intercalation of molecular and atomic species into quasi-free FLG was recently reported for K, Rb [195], ICl and IBr [196] using the vapour-phase method. In particular, partial intercalation of K and Rb was performed by means of a two-zone vapour-phase method at 210 and 160 • C, whereas the intercalation of ICl and IBr requires relatively low temperatures (just 35 • C).…”
Section: Intercalated Quasi-free Few-layer Graphenementioning
confidence: 99%
“…A large upshift of the G-peak in the Raman spectra is commonly observed upon intercalation, and it signifies that a large charge transfer occurs from (to) the molecular or atomic specie to (from) graphene. Furthermore, a strong anisotropy of resistance manifested in high c-axis (perpendicular to graphene planes) resistivity is expected [196] owing to a strong localization of the π -electronic orbitals in the graphene layers separated by ICl or IBr. The substantial reduction of the coupling between intercalated graphene layers makes these systems promising for studying excitonic condensates.…”
Section: Intercalated Quasi-free Few-layer Graphenementioning
confidence: 99%
“…Polar heteroatomic halogen GICs such as iodine monochloride (ICl), although barely studied, have been known since the 1950s, and offer access to GICs at room temperature overcoming the above-mentioned difficulties. [35][36][37][38][39][40][41][42][43] The stoichiometry of a stage-1 ICl GIC intercalation compound, i.e. consisting of alternating single layers of carbon and intercalant, has been suggested to be close to 10:1 in analogy with other acceptor intercalation compounds (e.g FeCl 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polar heteroatomic halogen GICs such as iodine monochloride (ICl), although barely studied, have been known since the 1950s and offer access to GICs at room temperature, overcoming the abovementioned difficulties. The stoichiometry of a stage 1 ICl-GIC intercalation compound, i.e., consisting of alternating single layers of carbon and intercalant, has been suggested to be close to 10:1 in analogy with other acceptor intercalation compounds (e.g., FeCl 3 ). , Early structural analysis by Abe et al reported an interlayer spacing of 7.14 Å. Moret et al performed a detailed crystallographic analysis and suggested that the stage 1 GIC exhibits an incommensurate structure with a large unit cell, proposing up to nine ICl molecules in the unit cell . Later, extended X-ray absorption spectroscopy and near-edge X-ray absorption fine structure analysis (EXAFS) showed characteristic distances assigned to I–Cl and halogen-carbon bonds .…”
Section: Introductionmentioning
confidence: 99%
“…The electronic properties of the AB-stacked and AAstacked bilayer graphene (BLG) structures, their optical characteristics and excitonic phases have been the subject of many experimental and theoretical works . Beside the fact that the AB-BLG is very promising for technological applications, the AA-BLG shows intriguing properties when exposed to the external electric field [1, 2, 5-7, 16, 27, 28, 30, 31] and a series of researches was done to fabricate such structures [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%